Conn Smythe: the complexity and contradiction of a hockey entrepreneur. Issue 9 (1st September 2020) - Stevens, Julie
Abstract: Entrepreneurs are touted as catalysts for both economic stabilization and growth within various industries. In the case of men's professional hockey in North America, one such entrepreneur was Conn Smythe, owner of the Toronto Maple Leaf franchise and Maple Leaf Gardens. This paper summarizes Smythe's success in relation to internal characteristics, such as personal attitude, skills and expertise, and external characteristics such as cultural, political and economic change. His influence upon the professional sport industry is also discussed in both positive and negative terms. In conclusion, the complexity and contradiction of Con Smythe as a hockey entrepreneur are examined.